Gut microbiota and metabonomics used to explore the mechanism of Qing'e Pills in alleviating osteoporosis. (31st December 2022) - Xie, Hui; Hua, Zhengying; Guo, Mengyu; Lin, Shangyang; Zhou, Yaqian; Weng, Zebin; Wu, Li; Chen, Zhipeng; Xu, Zisheng; Li, Weidong
Abstract: Context: The traditional Chinese medicine Qing'e Pills (QEP) has been used to treat postmenopausal osteoporosis (PMO). Objective: We evaluated the regulatory effects of QEP on gut microbiota in osteoporosis. Materials and methods: Eighteen female SD rats were divided into three groups: sham surgery (SHAM), ovariectomized (OVX) and ovariectomized treated with QEP (OVX + QEP). Six weeks after ovariectomy, QEP was administered to OVX + QEP rats for eight weeks (4.5 g/kg/day, i.g.). After 14 weeks, the bone microstructure was evaluated. Differences in gut microbiota were analysed via 16S rRNA gene sequencing. Changes in endogenous metabolites were studied using UHPLC-Q-TOF/MS technology. GC–MS was used to detect short-chain fatty acids. Furthermore, we measured serum inflammatory factors, such as IL-6, TNF-α and IFN-γ, which may be related to gut microbiota. Results: OVX + QEP exhibited increased bone mineral density (0.11 ± 0.03 vs. 0.21 ± 0.02, p < 0.001) compared to that of OVX. QEP altered the composition of gut microbiota. We identified 19 potential biomarkers related to osteoporosis. QEP inhibited the elevation of TNF-α (38.86 ± 3.19 vs. 29.43 ± 3.65, p < 0.05) and IL-6 (83.38 ± 16.92 vs. 45.26 ± 3.94, p < 0.05) levels, while it increased the concentrations of acetic acid (271.95 ± 52.41 vs. 447.73 ± 46.54, p < 0.001), propionic acid (28.96 ± 5.73 vs. 53.41 ± 14.26, p < 0.01) and butyric acid (24.92 ± 18.97 vs. 67.78 ± 35.68, p < 0.05). Conclusions: These results indicate that QEP has potential of regulating intestinal flora and improving osteoporosis. The combination of anti-osteoporosis drugs and intestinal flora could become a new treatment for osteoporosis.